The Palliative Care in Heart Failure (PAL-HF) Trial: Rationale and Design - Mentz, Robert J. (Am Heart J, 2014)
BACKGROUND: The progressive nature of heart failure (HF) coupled with high mortality and poor quality of life mandates greater attention to palliative care as a routine component of advanced HF management. Limited evidence exists from randomized, controlled trials supporting the use of interdisciplinary palliative care in HF. METHODS: The Palliative Care in Heart Failure trial (PAL-HF) is a prospective, controlled, unblinded, single-center study of an interdisciplinary palliative care intervention in 200 patients with advanced HF estimated to have a high likelihood of mortality or re-hospitalization in the ensuing 6 months. The 6-month PAL-HF intervention focuses on physical and psychosocial symptom relief, attention to spiritual concerns and advanced care planning. The primary endpoint is health-related quality of life measured by the Kansas City Cardiomyopathy Questionnaire and the Functional Assessment of Chronic Illness Therapy with Palliative Care Subscale score at 6 months. Secondary endpoints include changes in anxiety/depression, spiritual well-being, caregiver satisfaction, cost and resource utilization, and a composite of death, HF hospitalization and quality of life. CONCLUSIONS: PAL-HF is a randomized, controlled clinical trial that will help evaluate the efficacy and cost-effectiveness of palliative care in advanced HF using a patient-centered outcome as well as clinical and economic endpoints.